Word processing primer - Waite, Mitchell. 4 0 16; Arca, Juli.; 5 (Peterborough, NH : McGraw Hill, 1982)
Presents an overview of the microcomputer word processing field detailing applications and describing equipment and programs.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Word processing (Office practice) -- 20; 20; 2